Method for preparing fine-grain ceramic by adjusting and controlling flash firing outside furnace through prefabricated metal wire switch
By prefabricating metal conductors on the surface of ceramic vegetative embryos and heating with external power supply, rapid heating and flash firing of ceramic materials at room temperature is achieved, solving the dependence of traditional flash firing technology on furnace body heating and grain growth problems, and high-density fine crystalline ceramic materials are prepared.
Patent Information
- Application Number
- CN202411757487.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing flash burning technology relies on traditional furnace body heating, limiting the flexibility of the experimental site and equipment, and easily leads to grain growth and low melting point elements during the furnace heating process.
The prefabricated metal wires on the surface of the ceramic vegetation are screen-printed and heated by external power supply, so that the ceramic vegetation is quickly heated to the flash burning temperature at room temperature, achieving flash burning outside the furnace.
This method can achieve flash firing at a lower voltage, and prepare ceramic materials with high density and fine crystal structure, avoiding the problems of grain growth and low melting point element volatility, while reducing the dependence on high-voltage equipment and safety hazards.
Smart Images

Figure CN119591398A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic sintering, and in particular relates to a method for preparing fine-grained ceramics by flash-firing outside a prefabricated metal conductor switch-controlled furnace. Background Art
[0002] The structure of a material determines its properties. Compared with traditional polycrystalline ceramics, fine-grained ceramics with significantly refined grains have significantly improved properties, showing higher strength, hardness and toughness, enhanced diffusivity, higher thermal expansion coefficient, lower thermal conductivity, higher resistivity and superior soft magnetic properties. Controlling grain growth during sintering and achieving sufficient densification is the key to obtaining high-density and fine-grained ceramic materials. The two basic sintering behaviors, densification and grain growth, have the same driving force in thermodynamics and compete with each other. They can only be distinguished by regulating the sintering process and taking advantage of their kinetic differences. Among them, increasing the sintering rate is the most commonly used and effective method.
[0003] Commonly used rapid sintering technologies include microwave sintering, spark plasma sintering and flash sintering. Spark plasma sintering uses high-temperature plasma generated by large current to sinter the material while also applying additional pressure to it. It has the advantages of fast heating rate and short sintering time, but also has problems such as uneven densification of the sintered body. Microwave sintering uses the heat released by the interaction between microwaves and materials to quickly heat the material and complete the sintering. It has the characteristics of fast heating rate, but this method is selective to materials and must absorb microwaves to be more effective, which has certain limitations.
[0004] The new rapid heating flash firing technology utilizes electric field assisted sintering technology to apply appropriate AC or DC voltage at both ends of the ceramic green body to form a conductive path in the ceramic green body. Under the action of Joule heat, the sample is highly densified in just a few seconds to a few minutes. It has the advantages of rapid heating, activation of particle surface, and flexible process adjustment. Many studies have shown that it has the effect of promoting densification and inhibiting grain growth, and is very suitable for the sintering of structural ceramic materials.
[0005] However, the existing flash burning technology cannot get rid of the limitation of heating furnace, that is, the excitation temperature of flash burning depends on the heating of traditional furnace body, which puts forward certain requirements for experimental site and equipment; at the same time, the sample heats up slowly with the furnace before flash burning, which inevitably causes problems such as grain growth and volatilization of low melting point elements in the process. In order to get rid of furnace heating and realize flash burning technology, many researchers have developed room temperature flash burning technology through various paths, such as flash burning zinc oxide at room temperature by adding ultra-high pressure to generate high temperature arc, and adding ethanol to the blank, using ethanol volatilization to promote the generation of high temperature arc under high pressure conditions to quickly perform Joule heating on the sample and obtain a dense blank; in addition, there is also the use of water-assisted high voltage room temperature conduction to perform Joule heating on zinc oxide blank, and the use of graphene added to the blank to assist in the construction of internal heat conduction paths, which realizes the preparation of graphene composite ceramic materials by room temperature flash burning.
[0006] In the prior art, the preparation of fine-grained ceramics by flash firing at room temperature with high voltage has high requirements for high-voltage equipment. At the same time, the high-temperature arc generated by high voltage has great safety hazards and is easy to cause personal injury. The use of liquid (water or ethanol) to assist flash firing at room temperature, due to the evaporation of the liquid, leaves gaps, it is difficult to obtain high-density and high-strength fine-grained ceramics. The method of adding graphene to the blank to assist in the construction of internal heat conduction paths is helpful for graphene-toughened composite materials, but it is not applicable to the preparation of high-insulation ceramic materials. Summary of the invention
[0007] Based on the above-mentioned shortcomings and deficiencies in the prior art, one of the objects of the present invention is to solve at least one or more of the above-mentioned problems in the prior art. In other words, one of the objects of the present invention is to provide a method for preparing fine-grained ceramics by flash firing outside a prefabricated metal conductor switch regulating furnace that meets one or more of the above-mentioned needs.
[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0009] A method for preparing fine-grained ceramics by flash firing outside a prefabricated metal conductor switch control furnace comprises the following steps:
[0010] (1) Prefabricating a metal wire of a preset width on the surface of a blank using metal slurry by screen printing and curing the metal slurry to obtain a ceramic green body prefabricated with the metal wire; placing the ceramic green body prefabricated with the metal wire in air, providing electrodes at both ends of the ceramic green body, and connecting the electrodes to a power source through the wires;
[0011] (2) Turn on the power supply, adjust the current to control the size of the joule, and control the temperature rise rate and peak temperature;
[0012] (3) When the metal wire melts, it automatically switches to the target voltage value set by the power supply. After the current of the ceramic green body rises to the target current density value, the constant current value is maintained for the target time, and the power supply is turned off to obtain dense and fine-grained ceramics.
[0013] As a preferred solution, the metal slurry is platinum slurry, silver slurry or tin slurry.
[0014] As a preferred embodiment, in step (1), the curing temperature is 60-600°C.
[0015] As a preferred solution, in step (1), the preset width is 0.2-1.2 mm.
[0016] As a preferred solution, in step (2), the adjustable range of the current is 0.1-50A.
[0017] As a preferred embodiment, in step (2), the temperature rise rate is 10-200° C. / s, and the peak temperature is determined according to the melting point of the metal wire.
[0018] As a preferred solution, in step (3), the target current density value is 100 to 1000 mA / mm 2 , the target voltage is 50~300V / cm.
[0019] As a preferred solution, in step (3), the target duration is 30 to 180 seconds.
[0020] As a preferred embodiment, the blank is in the shape of a long strip, a round piece or a dog bone.
[0021] As a preferred embodiment, the powder used for the blank is titanium dioxide, zinc oxide, vanadium oxide, cerium oxide, aluminum oxide, barium titanate, potassium sodium niobate or sodium bismuth titanate.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention utilizes screen printing to prepare metal wires on the surface of a ceramic blank. The prefabricated metal wires are heated by an external power supply so that the temperature of the ceramic blank rises rapidly. Since the prefabricated metal wires have a certain melting point, they will fuse when the temperature reaches a certain value. At this time, the ceramic sample under high temperature excitation can be flash-burned at a relatively low voltage to prepare fine-grained ceramics.
[0024] By adjusting the type of metal in the metal wire (such as tin with a low melting point and silver with a higher melting point) and the width of the wire (according to Joule's law, the thinner the wire, the greater its resistance and the greater its Joule heat under the same current), the peak temperature and temperature rise rate of the sample can be adjusted; the rapid heating of the metal wire can also ensure that the ceramic grains do not grow before flash burning occurs and avoid the volatilization of low-melting-point elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a structural diagram of preparing fine-grained ceramics by flash firing outside a furnace for regulating the prefabricated metal conductor switch of Example 1 of the present invention;
[0026] Figure 2 This is a SEM image of the fine-grained zinc oxide ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to more clearly illustrate the embodiments of the present invention, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other accompanying drawings and other implementation methods can be obtained based on these accompanying drawings without creative work.
[0028] Embodiment 1:
[0029] This embodiment uses a low melting point tin wire to flash the zinc oxide ceramic, and the specific process is as follows:
[0030] (1) Pressing the green body;
[0031] Polyvinyl alcohol (PVA) was added to deionized water to prepare a 10 wt% binder, and the nano zinc oxide powder and the binder were mechanically mixed and dried; 0.5 g of the dried mixed powder was added to a mold and pressed into a dog bone shape at a pressure of 300 MPa. The size of the blank was 20×3×2 mm. 3 .
[0032] (2) Debonding treatment;
[0033] The pressed green body was placed in a muffle furnace, heated to 400°C at a heating rate of 2°C / min and kept at that temperature for 2 hours, and then cooled in the furnace to obtain a ceramic green body.
[0034] (3) coating electrodes;
[0035] In order to reduce the contact resistance between the ceramic green body and the circuit, high-temperature silver paste is applied to both ends of the ceramic green body and baked at 500°C for 10 minutes to solidify the silver paste;
[0036] (4) Prefabricated tin wire;
[0037] A thin line with a width of 1 mm was coated between the two electrodes using screen printing tin paste and dried in an oven at 60 °C to obtain the following Figure 1 Silkscreen conductors shown.
[0038] (5) Figure 1 As shown, the ceramic green body is connected to an AC power source with a copper wire (i.e., a conductor) with a radius of 0.5 mm to prepare for flash firing;
[0039] (6) At room temperature, after turning on the power switch, the voltage value is preset to 400V (electric field strength is 200V / cm), the current value is 0.6A (current density is 100mA / mm 2 ); After turning on the start button, the current stabilizes at 0.6A. At this time, the tin wire continues to heat up under the action of the current, and the temperature of the blank rises to a peak temperature of 250°C at a rate of 50°C / s; after the 0.6A current continues to act for 1 minute, the tin wire at some positions melts into a spherical shape under the action of heat, causing the tin wire to disconnect, the current disappears, and the voltage at both ends of the blank returns to 400V. At this time, under the action of 250°C temperature and 400V voltage, the current of the sample increases rapidly at a rate of 10mA / s, and finally the current reaches the preset value of 0.6A and enters the stable period, entering the current control mode. This state is maintained for 30s, and the material is sintered densely, realizing the sintering of zinc oxide ceramic materials.
[0040] like Figure 2 As shown, the zinc oxide sintered at room temperature in this embodiment has a higher density, and the grain size is in the range of 1-3 μm.
[0041] Embodiment 2:
[0042] This embodiment uses medium-low melting point silver wire to flash-sinter titanium dioxide ceramics, and the specific process is as follows:
[0043] (1) Pressing the green body;
[0044] Polyvinyl alcohol (PVA) was added to deionized water to prepare a 10 wt% binder, and nano-anatase titanium dioxide powder was mechanically mixed with the binder and dried; 0.4 g of the dried mixed powder was added to a mold and pressed into a dog bone shape at a pressure of 300 MPa. The size of the green body was 20×3×2 mm. 3 .
[0045] (2) Debonding treatment;
[0046] The pressed green body was placed in a muffle furnace, heated to 400°C at a heating rate of 2°C / min and kept at that temperature for 2 hours before being cooled in the furnace.
[0047] (3) coating electrodes;
[0048] In order to reduce the contact resistance between the ceramic green body and the circuit, high-temperature silver paste is applied to both ends of the ceramic green body;
[0049] (4) Prefabricated silver wire;
[0050] A thin line with a width of 0.5 mm was coated between the two electrodes using screen-printed silver paste and baked at 500 °C for 10 min to cure the silver paste.
[0051] (5) The titanium dioxide green body was connected to an AC power source with a copper wire with a radius of 0.5 mm to prepare for flash firing.
[0052] (6) At room temperature, after turning on the power switch, the voltage value is preset to 500V (electric field strength is 250V / cm), the current value is 1.2A (current density is 200mA / mm 2 ); After turning on the start button, the current stabilizes at 1.2A. At this time, the silver wire continues to heat up under the action of the current, and the temperature of the blank rises to a peak temperature of about 800℃ at a rate of 100℃ / s; after the 1.2A current continues to act for 1 minute, the silver wire in some positions oxidizes and shrinks under the action of heat and melts, the current disappears, and the voltage at both ends of the blank returns to 500V. At this time, the sample is at a temperature of about 800℃ and a voltage of 500V, and the current increases rapidly at a rate of 10mA / s. Finally, the current reaches the preset value of 1.2A and enters the stable period, entering the current control mode. This state is maintained for 60s, and the material is sintered densely, realizing the sintering of zinc oxide ceramic materials.
[0053] Embodiment 3:
[0054] This embodiment uses a high melting point platinum wire to flash burn alumina ceramics, and the specific process is as follows:
[0055] (1) Pressing the green embryo;
[0056] Polyvinyl alcohol (PVA) was added to deionized water to prepare a 10 wt% binder, and the nano-aluminum oxide powder was mechanically mixed with the binder and dried; 0.4 g of the dried mixed powder was added to a mold and pressed into a dog bone shape at a pressure of 300 MPa. The size of the green body was 20×3×2 mm. 3 .
[0057] (2) Debonding treatment;
[0058] The pressed green body was placed in a muffle furnace, heated to 400°C at a heating rate of 2°C / min and kept at that temperature for 2 hours before being cooled in the furnace.
[0059] (3) coating electrodes;
[0060] In order to reduce the contact resistance between the ceramic green body and the circuit, high-temperature silver paste is applied to both ends of the ceramic green body;
[0061] (4) Prefabricated platinum wire;
[0062] A thin line with a width of 0.3 mm was coated between the two electrodes using screen-printed platinum paste and baked at 600 °C for 10 min to cure the paste.
[0063] (5) The aluminum oxide green body is connected to an AC power source with a copper wire with a radius of 0.5 mm to prepare for flash firing.
[0064] (6) At room temperature, after turning on the power switch, the voltage value is preset to 600V (electric field strength is 300V / cm) and the current value is 2.4A (current density is 400mA / mm 2 ); After turning on the start button, the current stabilizes at 2.4A. At this time, the platinum wire continues to heat up under the action of the current, and the temperature of the blank rises to a peak temperature of about 1100℃ at a rate of 200℃ / s. After the 2.4A current continues to act for about 1 minute, part of the platinum wire oxidizes, shrinks and melts under the action of heat, the current disappears, and the voltage at both ends of the blank returns to 600V. At this time, under the temperature of about 1100℃ and the voltage of 600V, the current of the sample increases rapidly at a rate of 10mA / s, and finally the current reaches the preset value of 2.4A and enters the stable period, entering the current control mode. This state is maintained for 120s, the material is sintered densely, and the sintering of alumina ceramic material is achieved.
[0065] In view of the numerous embodiments of the scheme of the present invention, the raw materials and dosage involved can be selected according to actual needs within the limited range, and the experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here, but the content required to be verified and the final conclusion obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be explained one by one here.
[0066] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing fine-grained ceramics by flash firing outside a prefabricated metal conductor switch control furnace, characterized in that: The following steps are involved: (1) Prefabricating a metal wire of a preset width on the surface of a blank using metal slurry by screen printing and curing the metal slurry to obtain a ceramic green body prefabricated with the metal wire; placing the ceramic green body prefabricated with the metal wire in air, providing electrodes at both ends of the ceramic green body, and connecting the electrodes to a power source through the wires; (2) Turn on the power supply, adjust the current to control the size of the joule, and control the temperature rise rate and peak temperature; (3) When the metal wire melts, it automatically switches to the target voltage value of the set power supply. After the current of the ceramic green body rises to the target current density value, the constant current value is maintained for the target time, and the power supply is turned off to obtain dense and fine-grained ceramics.
2. The method according to claim 1, characterized in that The metal paste is platinum paste, silver paste or tin paste.
3. The method according to claim 2, characterized in that In the step (1), the curing temperature is 60-600°C.
4. The method according to claim 1, characterized in that In the step (1), the preset width is 0.2-1.2 mm.
5. The method according to claim 1, characterized in that In the step (2), the adjustable range of the current is 0.1-50A.
6. The method according to claim 1, characterized in that In the step (2), the temperature rise rate is 10-200° C. / s, and the peak temperature is determined according to the melting point of the metal wire.
7. The method according to claim 1, characterized in that In step (3), the target current density is 100-1000 mA / mm 2 , the target voltage is 50~300V / cm.
8. The method according to claim 1, characterized in that In the step (3), the target duration is 30 to 180 seconds.
9. The method according to any one of claims 1 to 8, characterized in that: The blank is in the shape of a disc, a strip or a dog bone.
10. The method according to any one of claims 1 to 8, characterized in that: The powder used in the blank is titanium dioxide, zinc oxide, vanadium oxide, cerium oxide, aluminum oxide, barium titanate, potassium sodium niobate or bismuth sodium titanate.
Citation Information
Patent Citations
Lanthanum chromate ceramic and preparation method thereof
CN110294629A
Ceramic room-temperature sintering method
CN113307624A
Ceramic sintering method and ceramic
CN113307638A
Rare earth doped zinc oxide voltage-sensitive ceramic, preparation method and application thereof
CN114349495A
Conductive paste for high-speed calcination
JP2009081033A